1997
DOI: 10.1258/1357633971930346
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry: ‘tele’ yes, but what about the ‘psychiatry’?

Abstract: To investigate what is lost or gained in a psychiatric evaluation when it takes place via telepsychiatry we compared the interrater reliability between two psychiatrists interviewing 63 subjects in an observer/interviewer split configuration in telepsychiatry and same-room settings. The measures used were the BPRS and interviewer ratings from a semi-structured interview. Patients also rated their experience. There were some clear differences between the telepsychiatry and same-room evaluations. Despite these v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 3 publications
3
70
0
Order By: Relevance
“…Common limitations in the systematic reviews were: grading of the evidence was not evident in the recommendations; studies were assessed for quality but were not linked to recommendations; all of the systematic reviews reported on the same 10 RCTs; 6,58-66 two child and adolescent RCTs [67][68] and two of the systematic reviews 23,39 included information from a further 8 moderate quality control studies. [69][70][71][72][73][74][75][76] The systematic reviews also only included studies up until 2008. The authors identified a further four RCTs published post 2008 which showed similar evidence to the studies in the systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Common limitations in the systematic reviews were: grading of the evidence was not evident in the recommendations; studies were assessed for quality but were not linked to recommendations; all of the systematic reviews reported on the same 10 RCTs; 6,58-66 two child and adolescent RCTs [67][68] and two of the systematic reviews 23,39 included information from a further 8 moderate quality control studies. [69][70][71][72][73][74][75][76] The systematic reviews also only included studies up until 2008. The authors identified a further four RCTs published post 2008 which showed similar evidence to the studies in the systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Telepsychiatry has been proven to be reliable and acceptable to both patients and providers for non-urgent care and has great potential for emergency care. [19][20][21][22][23][24] The initial evaluation of the MHEC-RAP during the establishment phase concluded that the program was helpful for both providers and patients. 25,26 The present study is part of a further evaluation and was designed to document longer-term changes in service use, identify gaps in services use and inform further service development.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of literature in telepsychiatry includes accounts of novel clinical demonstrations and descriptions of program projects, with a handful of empirical evaluations. 6 Several studies have compared psychiatric evaluation of the same patient face-to-face and over telemedicine [7][8][9][10][11] and have found high agreement between face-to-face and telemedicine. No such comparison has been reported in the jail setting.…”
Section: Introduction Rmentioning
confidence: 99%